Histological Study on the Fibrous Architecture of the Adrenal Gland During Postnatal Development in Buffalo - Kumar, Vishnudeo; Sethi, Ram Saran; Singh, Opinder (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study was conducted on the adrenal glands of 29 buffaloes ranging from day old to one year of age. The adrenal gland was fullydifferentiated into cortex and medulla in the day old buffalo calf and was completely surrounded by a dense fibrous capsule at thisstage. The capsule consisted of outer layer of loose connective tissue and inner layer of thick collagen fibres. The connective tissuetrabeculae made up of collagen and reticular fibres arose from the inner aspect of capsule and infiltrated the cortical parenchyma ofthe gland. The reticular fibres dominated in the inner aspect of the capsule and the proportion of reticular fibres was more in the zonaglomerulosa and outer zone of medulla, however, elastic fibres were not observed in any part of the gland up to one year of age. Theaverage thickness of the capsule increased with progression of age which was due to increase in the density of collagen fibres especiallyin the inner zone of capsule.
Keywords: Adrenal; Buffalo; Histological; Post natal